Lewis Acid Doping Induced Synergistic Effects on Electronic and Morphological Structure for Donor and Acceptor in Polymer Solar Cells. Issue 19 (29th March 2018) - Yan, Han; Chen, Jianya; Zhou, Ke; Tang, Yabing; Meng, Xiangyi; Xu, Xianbin; Ma, Wei
Abstract: Due to the attraction of optimizing the electronic structure beyond chemical synthesis, molecular doping has recently aroused wide interest in the field of organic solar cells. However, the selection of limited dopants confines its successful application. Inspired by the Lewis base characteristics of the photovoltaic materials, the Lewis acid as novel dopant is introduced in organic solar cells. In both fullerene and nonfullerene based blends, Lewis acid doping leads to increased photovoltaic performance. Detailed experiments reveal that Lewis acid doping has a synergistic effect on modifying the polymer's electronic properties and the acceptor's nanostructure even at low doping concentration, and these are simultaneously responsible for the device improvements. Based on the mechanism studies, it is proposed that the Lewis acid‐doped polymers anions produce induced dipole on the acceptor, this increases the intermolecular interaction and facilitates the morphology optimization. It is believed that the synergistic effect by Lewis acid doping greatly expands the application of doped organic solar cells, in concert with other existing methods to yield higher efficiency values. Abstract : Inspired by the Lewis base characteristics of the photovoltaic materials, the Lewis acid as novel dopant is introduced in organic solar cells. This study demonstrates that Lewis acid doping leads to increased photovoltaic performances. Further experiments reveal the synergistic effect on modifying the polymer's electronic properties and the acceptor's nanostructure by Lewis acid doping.